Breadcrumbs - Ursu, Anne.; McGuire, Erin. (New York : Walden Pond Press, 2011)
"Hazel and Jack are best friends until an accident with a magical mirror and a run-in with a villainous queen find Hazel on her own, entering an enchanted wood in the hopes of saving Jack's life " -- Provided by publisher.
008-012.
Keywords: Magic mirrors -- Fiction; Friendship -- Fiction; Rescues -- Fiction; Children -- Fiction; Magic -- Fiction; Mirrors -- Fiction; Best friends -- Fiction; Schools -- Fiction; Fantasy fiction